Spiritual Emotional Freedom Technique (SEFT) untuk Menurunkan Tingkat Kecemasan pada Pasien Hipertensi - Anam, Akhyarul; Upoyo, Arif Setyo; Isworo, Atyanti; Taufik, Agis; Sari, Yunita (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2021)
Abstract Hypertension is a state of increased blood pressure of more than 140/90 mmHg. Hypertension can be caused by individual anxiety and stress factors, and the state of hypertension can trigger anxiety in patients. Efforts that can be made to prevent and overcome anxiety in hypertension can be achieved with independent treatments or interventions such as Spiritual Emotional Freedom Tehnique (SEFT) spiritual therapy that is effective in maintaining blood pressure stability in the normal range. The purposed of this study was to determine of effectiveness health cadres and hypertension sufferers will increase their knowledge and skills on how to reduce anxiety through SEFT therapy. This program was carried out through health education through information transfer, discussion, demonstration, and ongoing assistance to cadres. Participants in this activity were 36 elderly Posyandu health cadres in Mersi Sub-District, Purwokerto Timur District. Knowledge scores were measured before and after education. The mean value of the pre test was known to be 52.78 while the mean value of the post test was 83.33. The results of paired t test analysis revealed that the value of p = 0,000 showed that there were significant differences between the scores of health cadres' knowledge scores on the understanding of SEFT therapy to reduce anxiety in patients with hypertension between before and after education. SEFT complementary therapy training can effectively improve the knowledge and skills of health cadres and hypertension sufferers in reducing anxiety.